2017
DOI: 10.4103/efh.efh_57_16
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' perceived educational needs to prevent and treat childhood obesity

Abstract: To provide students with an understanding of their role in preventing and treating childhood obesity, US medical schools need to provide students with childhood obesity-specific and general nutrition education. To build their self-efficacy in nutrition counseling, schools can use a combination of observation and practice led by skilled physicians and other healthcare providers. Increasing students' self-efficacy through training may help them overcome perceived barriers to childhood obesity prevention and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…About one-in-three reported that physicians are not trained to deal with childhood obesity. The current study re-emphasizes previous reports that medical students lack training related to childhood obesity care [13,14,17,18]. These observations are not surprising given the past reports about lack of comprehensiveness about childhood obesity care in medical school curricula [13,14,18] or the medical licensing examinations [19].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…About one-in-three reported that physicians are not trained to deal with childhood obesity. The current study re-emphasizes previous reports that medical students lack training related to childhood obesity care [13,14,17,18]. These observations are not surprising given the past reports about lack of comprehensiveness about childhood obesity care in medical school curricula [13,14,18] or the medical licensing examinations [19].…”
Section: Discussionsupporting
confidence: 84%
“…For example, using a nationally-representative sample from the United States (US), a study reported that less than 50% of graduating pediatric residents received the comprehensive training in childhood obesity care, with the least trained in behavioral management strategies and childhood obesity advocacy [13]. Another study suggested medical school curriculum should include more observations and practices for medical students to enhance students’ understanding of the childhood obesity epidemic and their roles in childhood obesity care [14]. Unfortunately, there is a lack of studies to inform the medical school curriculum development, especially from the point of view of students themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous literature examining HCP and obesity prevention has focused on their medical practice including, inpatient care (Tanda, Beverly, & Hughes, 2017), medical education (Cooke, Ash, & Goodell, 2017), or quality improvement (Watson-Jarvis, Driedger, & Fenton, 2017), instead of examining HCPs’ thoughts and beliefs regarding collaboration with community partners. Such community- and system-level interventions have been suggested to be more effective and are encouraged by the Academy of Pediatrics (Kuo et al, 2018) and Institute of Medicine (2010, 2012; NAS, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that medical students feel unfamiliar with obesity prevention and treatment. Self-reporting by pediatricians and primary care physicians demonstrated they also feel unprepared to successfully provide care to children with obesity (9)(10)(11).…”
Section: Study Importancementioning
confidence: 99%